ENHANCING MARKET TREND FORECASTING WITH EXPLAINABLE AI: A COMPARATIVE ANALYSIS OF DEEP LEARNING MODELS AND INTERPRETABILITY TECHNIQUES - Sisodia, Lokendra Singh; Khare, Ankur (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In financial analytics, investing and managing risk is deeply connected with forecasting market trends which is one of the most significant activities. The emergence of LSTM, GRU, and other deep learning technologies models have greatly improved forecasting accuracy. These deep learning techniques, however, are difficult to interpret and analyze which the makes the decision-making process in finance opaque. This research investigates the application of Explanatory AI techniques for improving models interpretability while still maintaining prediction accuracy. The study focuses on attention, saliency maps, Hapley Additive Explanations (SHAP), and Local Interpretable Model Agnostic Explanations (LIME) to determine importance of features for accurate prediction of market trends. It also aims to bridge a gap between explainable deep learning models (LSTM with attention, GRU with attention, and Transformer) and traditional models (LSTM, GRU) by conducting a comparison using financial time series datasets from SP500 and NASDAQ (2010-2024). For this purpose, the study will measure prediction accuracy using MAPE, RMSE, R Squared, as well as training time, all in the context of accuracy and interpretability trade-offs. From the data, we can see that the accuracy of the Transformer models was the highest ,whereas the LSTM + Attention models were more accurate and efficient, and therefore more appropriate for real time use cases. Besides SHAP, the feature importance analysis along with the attention-weighting tools showed market transparency by depicting important market figures. It highlights the primary purpose of XAI concerning compliance regulations, risk management, and AI assisted financial operations. Further studies should be conducted to delve into exploitation of hybrid deep learning models, sentiment oriented ones, and quantum AI in explainable market predictions that facilitate AI integration with industry transparency requirements.